A new species of Astragalus (Fabaceae) from the Irano-Turanian biodiversity hotspot: an integrative approach - Zahra Karbalaei; Ali Bagheri; Ali Asghar Maassoumi; Twan Rutten; Frank R. Blattner (Botanical Studies)
Abstract Background The genus Astragalus is the largest and one of the most diverse genera of flowering plants, particularly in the Northern Hemisphere, with a significant concentration of species in the Irano-Turanian region. Within this genus, section Hymenostegis is notable for its complexity and high levels of endemism, especially in northwestern Iran. During recent field explorations in West Azarbaijan province, a distinct population of Astragalus was identified, differing from known species within section Hymenostegis. This study aimes to describe and analyze this new species and clarify its relationship with closely related taxa using an integrative approach. Results Astragalus kuzehrashensis sp. nov. is described following detailed morphological comparisons with its closest relatives, A. chehreganii and A. hakkianus. The new species is distinguished by unique stipule characteristics, leaflet shape, inflorescence structure, and seed micromorphology. Molecular phylogenetic analysis using ITS and ycf1 sequences reveals that A. kuzehrashensis forms a clade with A. chehreganii and A. hakkianus, although it exhibits genetic differences. Genome size estimation confirms that A. kuzehrashensis is hexaploid (2n = 6x = 48), aligning it more closely with A. hakkianus than with the tetraploid A. chehreganii. The distinct morphological characters and genomic data support recognizing A. kuzehrashensis as a new species within section Hymenostegis. Conclusions The identification of A. kuzehrashensis underscores the importance of an integrative taxonomic approach, combining morphological, molecular, and cytogenetic data to resolve species boundaries within complex groups like Astragalus section Hymenostegis. This study highlights the rich biodiversity of the Irano-Turanian floristic region, emphasizing the need for ongoing exploration and conservation efforts, particularly in areas of high endemism. Our findings contribute to a deeper understanding of the taxonomy and evolutionary relationships within the genus Astragalus.